If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-1x + -2) = 0 Reorder the terms: 4(-2 + -1x) = 0 (-2 * 4 + -1x * 4) = 0 (-8 + -4x) = 0 Solving -8 + -4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -4x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -4x = 0 + 8 -4x = 0 + 8 Combine like terms: 0 + 8 = 8 -4x = 8 Divide each side by '-4'. x = -2 Simplifying x = -2
| 19-7p=-8p-(p-7) | | (7p-7)=10(2p+6)-7(-2+2p) | | 5x^4-8x^3-20x^2-4x+3=0 | | -6y+3x=-39 | | 4(y+2)-2(1-y)-4y=0 | | -33=2+5y | | 7(-2y+3)= | | 14+-2x=-3(x+1)-5 | | 55x+5y=45 | | 4(2x+5)+3x-2(x-7)=3(2x+7)-8 | | [Y]=5 | | -3x-2y=-2 | | 3(z-1)= | | 14-2x=-3(x+1)-5 | | 6(3+1)-30=3(2n-4) | | -6y+2y=-104 | | 4x-3+3=12 | | 9x-7=4x+9 | | 3x^2-5x+5=33 | | 10x-35+3x=5x-7a | | N+11=2 | | 2(3+x)=14x | | 11(4-3x)-5(2x+13)=194 | | -2y-42=-4(y+7) | | -2(y+9)= | | 5(c+2)=25 | | .4(12n-8)=26 | | 4(2x-7)=3(x+4) | | 2b+12b=70 | | 13x+(x+3)+(x+2)+(x+7)=40 | | 6x^3-5x^2+1=0 | | -3x-14+10x=-2 |